Potensi Ekstrak Etanol Kulit Batang Jabon (Anthocephalus cadamba (Roxb) Miq.) Sebagai Antiinflamasi - Bakri, Nur F.; Rusnaeni; Sasarari, Sarce M.; Gunawan, Elsye (Jurusan Biologi FMIPA Universitas Cenderawasih, 2024)
This study investigates the anti-inflammatory properties of an ethanol extract from Jabon plant stem bark in male mice using the Rat Hind Paw Edema method. Twenty-five male mice were divided into five groups: negative control (Na-CMC 1%), positive control (mefenamic acid), and three groups receiving the extract at doses of 50 mg/kg, 100 mg/kg, and 200 mg/kg. Measurements were taken every 30 minutes for three hours using a plethysmometer. Analysis with one-way ANOVA and Duncan's test revealed significant anti-inflammatory effects for all doses, with the most effective being 100 mg/kg, showing 93.42% inhibition. The results suggest Jabon plant extract as a promising anti-inflammatory agent.